An efficient bacterial laccase-mediated system for polyurethane foam degradation - Zhu, Xiaomin; Duan, Youren; Lu, Jianqi; Xia, Wei; Peng, Yujia; Liu, Jiawei; Dong, Weiliang; Jiang, Min (Frontiers in Microbiology, 2025)
Polyurethane (PU), a segmented block copolymer with chemically resistant urethane linkages and tunable architecture, presents persistent biological recycling challenges. This study presents a Bacterial Laccase-Mediated System (BLMS) derived from Bacillus subtilis for efficient degradation of polyester- and polyether-PU. Utilizing the laccase CotA and mediator 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), the BLMS demonstrated effective de polymerization of both commercial and self-synthesized PU foams, including polyester- and polyether-types. The weight loss of the self-synthesized polyester-foam and the commercial polyether-foam reached up to 21.24 ± 1.20% and 3.81 ± 0.36%, respectively. Subsequently, we detected oxygenated products such as ketones, alcohols, aldehydes, acids, esters, ethers, and 2,4– toluenediamine (2,4-TDA) indicating that bacterial laccase CotA exhibited redox catalytic activity toward PU. Moreover, an interesting phenomenon was observed during the degradation process that the solution turned purple. We predicted that this attribute to the enzymatic oxidation of ABTS to the radical cation ABTS·+, which subsequently reacts with 2,4-TDA to form the purple product. This study finds a plastic degrading enzyme capable of hydrolyzing urethane bonds in PU, offering a promising contribution to the development of a bio-based circular economy for PU biodegradation and recycling.